Event sustainability an analysis of wastes, impacts, and practices - Bernabe, Cynthia R.; Visbal, Martin Lorenzo O.; Garcia, Maria Rowena Jesusa R.; Diego, Eliza Rachel L.; Franchina, Steffano P.; Park, Seohee (2019)
Sustainability is a crucial aspect of today's events and event management practices. The negative environmental impact of events can easily be observed when it comes to food and beverage waste, improper waste disposal, and the use of non-renewable materials. this indicates that proper implementation of long-standing sustainability practices with the addition of new and innovative ideas is the key to combat this problem. This research deals with analyzing such practices in order to identify which must be applied in the events industry. An online survey was used to gather data for this research. Based on the data gathered, food and beverage, decorations, and collaterals are the top contributors to waste when it comes to events. furthermore, respondents also observed that although sustainable systems are already in place, a stricter and concise implementation must enforced. It is important to note that personal contributions are highly effective, especially for event stakeholders such as organizers, suppliers, and attendees, implying that sustainability is an activity that involves and affects everyone and everything.
Keywords: Sustainability; Events; Environment; Solid waste